Quantifying the economic survive across the EU using Markov probability chains - Ionescu, Romeo-Victor; Zlati, Monica Laura; Antohi, Valentin-Marian; Susanu, Irina Olimpia; Bărbuță-Mișu, Nicoleta (Technological and Economic Development of Economy, 2024)
The multiple global crisis has made the economies of the world’s countries, including EU’s economy, vulnerable through the downgrading of the pandemic and the subsequent outbreak of geo-political conflict. These two events had the effect of decelerating the European economy and increasing the poverty level of the population, even that these developments are weaker than in rest of the world. The main objective of the present scientific approach is to identify a risk function based on Markov probability chains and to assess the possibilities of economic recovery through a package of policies structured over different time horizons. The used methods consist of meta-analysis, statistical analysis and geo-spatial and temporal modelling. The results of the study capture the integrated developments of risk-generating macroeconomic elements such as inflation, unemployment, public debt growth in a regionally segregated manner. These elements are useful for supranational decision-makers to increase the economic survival rate after multiple shocks through our proposed policy package. First published online 14 March 2024